All Together Now: Modeling the Interaction of Neural With Non-neural Systems Using Organoid Models - Chukwurah, Evelyn; Osmundsen, Allison; Davis, Shannon W.; Lizarraga, Sofia B. (Frontiers in Neuroscience, 2019)
The complex development of the human nervous system has been traditionally studied using a combination of animal models, human post-mortem brain tissue, and human genetics studies. However, there has been a lack of experimental human cellular models that would allow for a more precise elucidation of the intricate dynamics of early human brain development. The development of stem cell technologies, both embryonic and induced pluripotent stem cells, has given neuroscientists access to the previously inaccessible early stages of human brain development. In particular, the recent development of three-dimensional culturing methodologies provides a platform to study the differentiation of stem cells in both normal development and disease states in a more in-vivo like context. Three-dimensional neural models or cerebral organoids possess an innate advantage over two-dimensional neural cultures as they can recapitulate tissue organization and cell type diversity that resemble the developing brain. Brain organoids also provide the exciting opportunity to model the integration of different brain regions in vitro. Furthermore, recent advances in the differentiation of non-neuronal tissue from stem cells provides the opportunity to study the interaction between the developing nervous system and other non-neuronal systems that impact neuronal function. In this review, we discuss the potential and limitations of the organoid system to study in vitro neurological diseases that arise in the neuroendocrine and the enteric nervous system or from interactions with the immune system.